2013
DOI: 10.1016/j.cca.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hemoglobin F levels in pregnant women unaffected by clinical fetomaternal hemorrhage

Abstract: Complete automation of high-performance liquid chromatography (HPLC) for determination of hemoglobin F (%Hb F) and hemoglobin A1c (%Hb A1c) levels has made this procedure available in many clinical laboratories. However, the physiological changes in %Hb F during pregnancy and the effects of physiological and supraphysiological levels of %Hb A1c on measurement of %Hb F have not been studied extensively. Simultaneous determination of %Hb F and %Hb A1c was conducted in 490 blood samples obtained before (n = 21), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
3
2
0
Order By: Relevance
“…Our study showed higher HbF levels in women, but the difference was not significant, similar to a study by Chang et al [11] Multivariate analysis showed that risk factors, such as age and sex, have a generally weak effect relative to genetic determinants. The HbF level in non-pregnant women in our study and in those in a Japanese study was similar, despite genetic differences between these two populations, confirming a standard level of 0.7% among non-pregnant women [12]. The pregnant women in our study were probably mostly in the 3rd trimester, based on the Japanese study.…”
Section: Foetal Haemoglobin Levels and The Prevalence Of Hpfhsupporting
confidence: 82%
See 2 more Smart Citations
“…Our study showed higher HbF levels in women, but the difference was not significant, similar to a study by Chang et al [11] Multivariate analysis showed that risk factors, such as age and sex, have a generally weak effect relative to genetic determinants. The HbF level in non-pregnant women in our study and in those in a Japanese study was similar, despite genetic differences between these two populations, confirming a standard level of 0.7% among non-pregnant women [12]. The pregnant women in our study were probably mostly in the 3rd trimester, based on the Japanese study.…”
Section: Foetal Haemoglobin Levels and The Prevalence Of Hpfhsupporting
confidence: 82%
“…No association was found in our study between HbF and sex or pregnancy, whereas other studies have shown the opposite [11,12]. Our study showed higher HbF levels in women, but the difference was not significant, similar to a study by Chang et al [11] Multivariate analysis showed that risk factors, such as age and sex, have a generally weak effect relative to genetic determinants.…”
Section: Foetal Haemoglobin Levels and The Prevalence Of Hpfhsupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of SNPs may have implications in a disease, such as increased HbF levels in common and complex diseases or conditions, e.g., drug-induced conditions, SCD, β-thalassemia, anemia, diabetes, chronic kidney failure, malignancies, or obesity in many regions of the world, such as Europe, the Middle East, and Southeast Asia, including Malaysia [ 20 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Several SNPs, such as rs11886868, rs766432, rs9399137, rs742144, rs9399137, rs28384513, and rs4671393, are associated with erythropoiesis and HbF augmentation ( Table 1 and Figure 2 ) [ 45 , 46 , 47 ].…”
Section: Polymorphisms Regulate the Expression Of Fetal Hemoglobinmentioning
confidence: 99%
“…The HbF level can increase when the erythropoietic process is stressed (Davis, ). As pregnancy is accompanied by an increase in the circulating blood volume of 40%, acute erythropoiesis that occurs in the first trimester may contribute to the elevation of first‐trimester HbF levels (Yamada et al, ). Normal adult erythrocytes contain 1–2% HbF.…”
mentioning
confidence: 99%